Detailed Photoisomerization Dynamics of a Green Fluorescent Protein Chromophore Based Molecular Switch - Chen-Wei Jiang; Ai-Ping Fang; Di Zhao; Hong-Rong Li; Rui-Hua Xie; Fu-Li Li (International Journal of Photoenergy)
With density-functional-based nonadiabatic molecular dynamics simulations, trans-to-cis and cis-to-trans photoisomerizations of a green fluorescent protein chromophore based molecule 4-benzylidene-2-methyloxazol-5(4H)-one (BMH) induced by the excitation to its S1 excited state were performed. We find a quantum yield of 32% for the trans-to-cis photoisomerization of BMH and a quantum yield of 33% for its cis-to-trans photoisomerization. For those simulations that did produce trans-to-cis isomerization, the average S1 excited state lifetime of trans-BMH is about 1460 fs, which is much shorter than that of cis-BMH (3100 fs) in those simulations that did produce cis-to-trans isomerization. For both photoisomerization processes, rotation around the central C2=C3 bond is the dominant reaction mechanism. Deexcitation occurs at an avoided crossing near the S1/S0 conical intersection, which is near the midpoint of the rotation.